2011
DOI: 10.1093/petrology/egr059
|View full text |Cite
|
Sign up to set email alerts
|

Melting of a Two-component Source beneath Iceland

Abstract: New trace element and Hf^Nd isotope data on post-glacial basalts from Iceland' s main rift zones are used in conjunction with literature data to evaluate the relative importance of source heterogeneity and the melting process for the final melt composition. Correlations between Hf and Nd isotope compositions and trace element ratios indicate that at least two source components are sampled systematically as a function of the degree and pressure of melting beneath Iceland. Strong depletion in Rb, Ba, U and Th an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 105 publications
3
83
0
Order By: Relevance
“…1). Koornneef et al (2012) previously reported their major and trace element and Hf and Nd isotope composition. In addition to the samples from the Reykjanes Peninsula (RP, n = 10), the Western Volcanic Zone (WV, n = 7), and the Northern Volcanic Zone (NV, n = 8), we re-analysed four samples from Theistareykir, a small area in the Northern Volcanic Zone, that were previously analysed by Stracke et al (2003aStracke et al ( , 2006 for their U, Th, Pa and Ra concentrations and isotope ratios.…”
Section: Sample Preparation and Analytical Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Koornneef et al (2012) previously reported their major and trace element and Hf and Nd isotope composition. In addition to the samples from the Reykjanes Peninsula (RP, n = 10), the Western Volcanic Zone (WV, n = 7), and the Northern Volcanic Zone (NV, n = 8), we re-analysed four samples from Theistareykir, a small area in the Northern Volcanic Zone, that were previously analysed by Stracke et al (2003aStracke et al ( , 2006 for their U, Th, Pa and Ra concentrations and isotope ratios.…”
Section: Sample Preparation and Analytical Techniquesmentioning
confidence: 99%
“…In Icelandic rocks, correlations between major elements and trace element ratios and long-lived isotopes suggest that melting of at least two components, one isotopically depleted and one isotopically enriched, is required to explain the observed trends (Wood, 1981;Elliott et al, 1991;Maclennan et al, 2003;Stracke et al, 2003b;Kokfelt et al, 2006;Maclennan, 2008a;Stracke and Bourdon, 2009;Peate et al, 2010;Koornneef et al, 2012). Although the nature of the enriched Icelandic source component remains controversial, most previous studies favoured ancient recycled oceanic crust, present in form of small-scale mafic components (e.g., Chauvel and Hémond, 2000;Skovgaard et al, 2001;Stracke et al, 2003b;Kokfelt et al, 2006;Peate et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations